An overview of chemically induced rodent models for sporadic colorectal cancer: Histopathological and translational perspectives - Sarmiento-Machado, Luis Manuel [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Romualdo, Guilherme Ribeiro [UNESP]; Barbisan, Luís Fernando (My University, 2024)
Globally, colorectal cancer (CRC) is one of the most frequently diagnosed human gastrointestinal neoplasia and the second leading cause of cancer-related death in both men and women. Despite considerable efforts currently devoted to the study of the biology and treatment of CRC, patient prognosis and survival are still poor. Sporadic CRC is a complex multistep disease and usually emerges in the setting of lifestyle and dietary changes mainly observed in industrialized countries with high human development index (HDI) (westernized style). The molecular pathogenesis of sporadic CRC presents genetic heterogeneity with APC, RAS, PIK3CA, TGFBR, SMAD4, and TP53 mutations usually detected during the progression of this malignancy. The establishment of sporadic CRC models has become essential for both basic and translational research to improve our understanding of the pathophysiology, unravel new molecular drivers, and preventive/therapeutic improvement of this malignancy. Chemically induced rodent models of sporadic CRC recapitulate most key morphological and genetic/epigenetic events observed during the promotion and progression of this malignancy, establishing effective diagnostic and prevention strategies to be translated into clinical practice. The present review gathers the main features of the state-of-the-art evidence on chemically induced rodent models, widely applied for translational modelling of sporadic CRC with a specific focus on histopathology and prevention perspectives. Our narrative review reinforces the persistent value of these bioassays and encourages the use of multimodel strategies for further investigations.
Keywords: Chemically induced rodent models; Chemoprevention and preventive strategies; Preneoplastic and neoplastic lesions; Sporadic colorectal cancer